Genetic differentiation in populations of Canada geese ( Branta canadensis ) - Wagner, Carol E. Van; Baker, Allan J. (Canadian Journal of Zoology, 1986)
Electrophoretic data for 35 structural gene loci were obtained from 249 individuals in 11 populations of Branta canadensis across North America. Twenty-four loci were polymorphic in at least one population sample, average observed heterozygosity ranged from 0.031 to 0.083, Rogers' genetic distance ranged from 0.014 to 0.063, and Wright's measure of genetic structuring among populations was 0.065. Samples of B. c. minima from Willows, California, and B. c. interior from Akimiski Island, Northwest Territories, exhibited both the highest levels of genetic variability within populations and the greatest divergence from other populations. Principal coordinates analysis on the genetic distances, followed by nonmetric scaling in three dimensions and supplemented by construction of a minimum spanning tree, gave a more informative and less distorted picture of relationships among populations than cluster analysis. Differentiation in structural genes was neither equivalent to morphometric differentiation (in magnitude and pattern) nor consistent with conventional subspecies designations. This suggests that structural genes are selectively neutral in Branta canadensis and are differentiating through random drift, in contrast to morphometric characters which have diverged markedly under different selective pressures.